Different Patterns of Neural Activity Characterize Motor Skill Performance During Acquisition and Retention - Beroukhim-Kay, Dorsa; Kim, Bokkyu; Monterosso, John; Lewthwaite, Rebecca; Winstein, Carolee (Frontiers in Human Neuroscience, 2022)
Motor performance and learning have distinct behavioral and neural signatures and can be uniquely modulated by various informational and motivational factors. Contemporary frameworks describe four different motor learning mechanisms mapped onto specific neural regions which are key for motor skill acquisition: error-based learning (cerebellum), reinforcement learning (basal ganglia), cognitive strategies (prefrontal cortex), and use-dependent learning (motor cortex). However, little is known about the neural circuits engaged during skill acquisition that are modulated specifically by practice-based performance improvement and those that predict recall performance. Based on previous work, we hypothesize that brain activity during practice in primary motor cortex and basal ganglia 1) is associated with trial-by-trial practice performance and 2) is predictive of immediate recall performance. Leveraging the contemporary framework, we use a well-known task paradigm that primarily relies upon cognitive strategy, reinforcement, and use-based learning mechanisms to test our hypotheses. Forty neurotypical young adults were asked to practice a pinch force tracking task. Participants received performance feedback after each trial during practice. We used whole brain analysis of functional magnetic resonance imaging (fMRI) and behavioral performance measures (i.e., time-on-target and self-efficacy) during the practice phase to determine which brain activation patterns are 1) associated with trial-by-trial tracking performance and 2) predictive of immediate no-feedback retention performance. We observed brain activations in the frontal orbital cortex, putamen, amygdala, and insula correlated with tracking performance improvement during practice. In contrast, a different set of performance-related activated regions were observed that were associated with immediate retention performance that included the primary motor cortex, superior frontal gyrus, somatosensory cortex, angular gyrus, and parietal gyrus. Our findings demonstrate that improved practice performance and recall of a sensorimotor skill are correlated with distinct neural activity patterns during acquisition, drawing on different motor learning mechanisms during encoding. While motor performance improvements depend on both cortical and subcortical regions, motor skill recall depends primarily on prefrontal and motor cortices. We discuss possible interpretations for why our hypothesis regarding basal ganglia activity and retention performance was not supported. Understanding the different neural mechanisms engaged in motor performance and learning may inform novel interventions to enhance motor skill learning.